Developing refutation text to resolve students’ misconceptions in addition and subtraction of integers - Syarifah Fadillah; Utin Desy Susiaty (Beta: Jurnal Tadris Matematika, 2019)
[English]: Students’ misconceptions in addition and subtraction of integers need to be addressed since this topic is a prerequisite for students to learn advanced mathematics topics such as algebra. Having misconceptions in understanding the prerequisite concepts will hamper the acquisition and integration of new knowledge. The purpose of this study was to develop refutation text to resolve the misconception of students in addition and subtraction of integers. Refutation text was developed in the form of student worksheet adopting the development model from Borg and Gall (1983). Tryout of refutation text involved fifteen seventh-grade students. The study found that (1) The experts’ validation reveals that refutation text is suitable to be used as learning media for students on addition and subtraction of integers; (2) The refutation text implemented in the tryout was useful to resolve students’ misconception in addition and subtraction of integers; and (3) The practitioner’s assessment and students’ response showed that refutation text is practical. Drawing from the findings, we argue that the developed refutation text help students correcting their misconceptions in the topics and could be used by the teachers in the classroom practices. However, the refutation text needs to be extended to anticipate students’ mistake in interpreting word problems by providing some possible mistakes and its correction. Keywords: Misconceptions, Refutation text, Integers [Bahasa]: Miskonsepsi siswa dalam penjumlahan dan pengurangan bilangan bulat perlu diatasi karena materi ini merupakan prasyarat bagi siswa untuk mempelajari materi matematika lanjutan seperti aljabar. Kesalahan dalam memahami konsep prasyarat akan menghambat penerimaan dan integrasi pengetahuan baru. Penelitian ini bertujuan mengembangkan media pembelajaran refutation text untuk mengatasi miskonsepsi siswa dalam penjumlahan dan pengurangan bilangan bulat. Refutation text yang dikembangkan berbentuk Lembar Kerja Siswa (LKS) dengan merujuk pada model pengembangan Borg dan Gall (1983). Uji coba refutation text dilakukan pada 15 orang siswa SMP kelas VII. Hasil penelitian menunjukkan bahwa (1) hasil penilaian ahli menunjukkan refutation text layak digunakan sebagai media pembelajaran bagi guru dalam mengajarkan penjumlahan dan pengurangan bilangan bulat; (2) refutation text yang diterapkan di kelas uji coba efektif dalam mengatasi miskonsepsi siswa dalam penjumlahan dan pengurangan bilangan bulat; dan (3) hasil penilaian praktisi dan respon siswa menunjukkan bahwa refutation text praktis digunakan sebagai media pembelajaran untuk mengatasi miskonsepsi siswa. Dalam hal ini, refutation text yang dikembangkan membantu siswa memperbaiki kesalahan konsep pada materi penjumlahan dan pengurangan bilangan bulat dan bisa digunakan oleh guru di kelas. Namun, refutation text tersebut perlu dikembangkan untuk mengantisipasi kesalahan siswa dalam menafsirkan soal cerita dengan menyediakan beberapa kemungkinan kesalahan interpretasi dan perbaikan. Kata kunci: Miskonsepsi, Refutation text, Bilangan bulat